Experimental investigation of the mechanical properties of Al6061-TiB2-fly ash reinforced monolithic and hybrid composites - K Nithesh; Karthik B M; Sathyashankara Sharma; Gajanan Anne; Ananda Hegde (Materials Research Express)
This study investigates the mechanical properties of Al6061-TiB _2 -fly ash reinforced monolithic and hybrid composites, fabricated using the stir casting technique. The experiment involved the preparation of both monolithic composites by varying TiB2 (3–6 wt%) and hybrid composites by varying TiB _2 (1–3 wt%) and fly ash (3–5 wt%) within the Al6061 matrix. Preheated reinforcement particles were introduced to the matrix alloy under controlled stirring conditions to ensure proper dispersion. Mechanical testing was conducted on the fabricated composites to evaluate their hardness and tensile strength. The results indicate that the hybrid composites exhibit superior mechanical properties compared to the base Al6061 alloy and the monolithic composites. The hardness of the hybrid composites A1T3F (Al6061 + 1%TiB _2 + 3% fly ash) and A3T5F (Al6061 + 3%TiB _2 + 5% fly ash) were significantly improved, reaching 134 HV and 146 HV, respectively, compared to 74 HV for the base alloy. The tensile strength of the hybrid composites also exceeded that of the monolithic composites, demonstrating the synergistic reinforcement effect of TiB _2 and fly ash. However, attempts to incorporate higher levels of reinforcement (TiB _2 5% and fly ash 7%) were unsuccessful due to agglomeration issues. The results indicate that the hybrid composites provide a cost-effective solution with enhanced mechanical properties, making them a more economical and efficient alternative to monolithic composites reinforced solely with TiB _2 .